1989
DOI: 10.1063/1.343342
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence characterization of ZnSe doped with Ga by bulk and planar doping techniques in molecular-beam epitaxy

Abstract: Room-temperature and low-temperature (1.7-K) photoluminescence (PL) characteristics of heteroepitaxial ZnSe layers on GaAs which are doped with Ga by either conventional (bulk) or planar doping techniques are described. Low-temperature PL peaks at 2.27 and 2.0 eV involving deep acceptor levels are introduced by Ga doping, as well as newly reported shallow acceptor levels with binding energies of approximately 68 and 85 meV. The behavior of these peaks and the excitonic transitions is studied as a function of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Emission in this energy range may also be affected by the presence of Ga impurities. Reference 24 reported that Ga-doped ZnSe exhibited a peak around 2.0 eV when the Ga concentration was high, while a peak around 2.2 eV was more prominent when the Ga concentration was low [21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emission in this energy range may also be affected by the presence of Ga impurities. Reference 24 reported that Ga-doped ZnSe exhibited a peak around 2.0 eV when the Ga concentration was high, while a peak around 2.2 eV was more prominent when the Ga concentration was low [21].…”
Section: Resultsmentioning
confidence: 99%
“…5b and d). This transformation can be attributed to a competition between emission from shallow states near the band edge and emission from the impurities and native and extended defects that contributes to the DLE and Y 0 bands [21]. Thus, preparation of the ZnSe/GaAs interface with an As-rich surface and a Zn-PT is favorable to realizing ZnSe epilayers with lower impurity and defect densities and higher optical quality.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of ZnSe PL spectra at 1 atm (7 K) for (a) the same high purity undoped film, (b), (c), and (d) samples doped with the acceptors N, P, and As, respectively nated by bound excitons due to the intentional dopant (i.e., Ga, C1, N, P, or As). The DAP lines (2.55 to 2.75 eV) arise from shallow states of the majority dopant and of various residual impurities having the opposite polarity [42]. Broad 'midgap' PL bands are common in ZnSe and other 11-VI materials.…”
Section: Fig 2 Andmentioning
confidence: 99%
“…[9][10][11] The level emission at 2.05 and 2.27 eV has also been reported in ZnSe:Ga layers where Ga is positioned on the same column as Al in the periodic table and has a similar atomic radius to Al. 17,18 In the case of ZnSe:Ga layers, it has been found that the concentration of V Zn increases with the increase of incorporated Ga concentration and strong emission near 2.05 eV found in ZnSe:Ga is ascribed to a Ga Zn V Zn complex defect. 18,19 Consequently, it is expected that the radiative trap centers RD1 and RD2 found in a heavily doped ZnSe:Al layer are ascribed to an Al donor complex defect and a V Zn -related defect.…”
Section: Resultsmentioning
confidence: 98%